A Critique of Feuerbach’s Anthropological Thought in the German Ideology - Xinghui Chen (Studies in Social Science & Humanities, 2024)
The German Ideology is often seen as a sign of Marx’s creation of a new worldview, the so-called new worldview, which is the materialism of practice and history, i.e., the materialist conception of history. In the first chapter “Feuerbach” chapter, Marx criticized against Feuerbach’s anthropological thought based on the old materialism. In terms of anthropological thought, Feuerbach understood human beings as abstract beings as “classes”, while Marx pointed out that human beings are “real human beings”. This critique is not only important for the formation of the materialist conception of history, but also has many guiding values for the path of human emancipation in reality.